Penurunan Tingkat Kemiskinan dan Gini Ratio Melalui Common Effect Model: Studi Kasus Pembiayaan Ultra Mikro di Provinsi Jawa Timur - SJ, Chandra Julihandono (Direktorat Sistem Perbendaharaan, 2024)
The ultra micro financing (UMi) credit program constitutes one of the government's efforts to empower micro, small, and medium-sized enterprises (MSMEs). Ultra-micro entrepreneurs, who outnumber other business categories and contribute significantly to the local economy, are the target of this funding due to their limited access to capital finance. This study aims to examine the impact of UMi financing on the welfare of UMi debtors', with the goal of reducing poverty and inequality in East Java. Based on secondary data from the Ministry of Finance, this study uses a quantitative approach with panel data regression analysis. This study's findings that UMi financing enhances the economic value of debtors' enterprises, while its impact on reducing the gini ratio is limited, increased business turnover significantly contributes to lowering poverty levels. East Java poverty and population disparity are not significantly impacted by business assets. In the future, it is expected that UMi financing will be disbursed after updating the data on the number of ultra-micro entrepreneurs, and that the financing allocation ceiling will be increased to expand the reach of UMi financing distribution.